Updated assessment of risks and benefits of dolutegravir versus efavirenz in new antiretroviral treatment initiators in sub-Saharan Africa: modelling to inform treatment guidelines. Issue 3 (March 2020) - Phillips, Andrew N; Bansi-Matharu, Loveleen; Venter, Francois; Havlir, Diane; Pozniak, Anton; Kuritzkes, Daniel R; Wensing, Annemarie; Lundgren, Jens D; Pillay, Deenan; Mellors, John; Cambiano, Valentina; Jahn, Andreas; et al.
Summary: Background: The integrase inhibitor dolutegravir is being considered in several countries in sub-Saharan Africa instead of efavirenz for people initiating antiretroviral therapy (ART) because of superior tolerability and a lower risk of resistance emergence. WHO requested updated modelling results for its 2019 Antiretroviral Guidelines update, which was restricted to the choice of dolutegravir or efavirenz in new ART initiators. In response to this request, we modelled the risks and benefits of alternative policies for initial first-line ART regimens. Methods: We updated an existing individual-based model of HIV transmission and progression in adults to consider information on the risk of neural tube defects in women taking dolutegravir at time of conception, as well as the effects of dolutegravir on weight gain. The model accounted for drug resistance in determining viral suppression, with consequences for clinical outcomes and mother-to-child transmission. We sampled distributions of parameters to create various epidemic setting scenarios, which reflected the diversity of epidemic and programmatic situations in sub-Saharan Africa. For each setting scenario, we considered the situation in 2018 and compared ART initiation policies of an efavirenz-based regimen in women intending pregnancy, and a dolutegravir-based regimen in others, and a dolutegravir-based regimen, including in women intending pregnancy. We considered predicted outcomes over a 20-year period from 2019 to 2039, used a 3% discount rate, and a cost-effectiveness threshold of US$500 per disability-adjusted life-year (DALY) averted. Findings: Considering updated information on risks and benefits, a policy of ART initiation with a dolutegravir-based regimen rather than an efavirenz-based regimen, including in women intending pregnancy, is predicted to bring population health benefits (10 990 DALYs averted per year) and to be cost-saving (by $2·9 million per year), leading to a reduction in the overall population burden of disease of 16 735 net DALYs per year for a country with an adult population size of 10 million. The policy involving ART initiation with a dolutegravir-based regimen in women intending pregnancy was cost-effective in 87% of our setting scenarios and this finding was robust in various sensitivity analyses, including around the potential negative effects of weight gain. Interpretation: In the context of a range of modelled setting scenarios in sub-Saharan Africa, we found that a policy of ART initiation with a dolutegravir-based regimen, including in women intending pregnancy, was predicted to bring population health benefits and be cost-effective, supporting WHO's strong recommendation for dolutegravir as a preferred drug for ART initiators. Funding: Bill & Melinda Gates Foundation.